Workplace Stress, Presenteeism, Absenteeism, and Resilience Amongst University Staff and Students in the COVID-19 Lockdown - Van Der Feltz-Cornelis, Christina Maria; Varley, D.; Allgar, Victoria L.; de Beurs, Edwin (Frontiers in Psychiatry, 2020)
Background: This study explored how the COVID-19 outbreak and arrangements such as remote working and furlough affected work or study stress levels and functioning in staff and students at the University of York, UK. Methods: An invitation to participate in an online survey was sent to all staff and students in May-June 2020. We measured stress levels (VAS-scale, Perceived Stress Questionnaire(PSQ)), mental health (anxiety(GAD-7), depression(PHQ-9)), physical health (PHQ-15 and chronic medical conditions checklist, presenteeism and absenteeism levels(iPCQ). We explored demographic and other characteristics as factors which may contribute to resilience and vulnerability for the impact of COVID-19 on stress. Results: 1,055 staff and 925 students completed the survey. Ninety-eight per cent of staff and seventy – eight per cent of students worked or studied remotely. 7% of staff and 10% of students reported sickness absence. 26% of staff and 40% of the students experienced presenteeism. 22% - 24% of staff reported clinical-level anxiety and depression scores, and 37.2% and 46.5% of students. Staff experienced high stress levels due to COVID-19, (66.2%, labelled vulnerable) and 33.8% experienced low stress levels (labelled resilient). Students were 71.7% resilient versus 28.3% non-resilient. Predictors of vulnerability in staff were having children (OR = 2.23; CI(95) = 1.63-3.04) and social isolation (OR = 1.97; CI(95) = 1.39-2.79) and in students, being female (OR = 1.62; CI(95) = 1.14-2.28), having children (OR = 2.04; CI(95) = 1.11-3.72), and social isolation (OR = 1.78; CI(95) = 1.25-2.52). Resilience was predicted by exercise in staff (OR = 0.83; CI(95) = 0.73-0.94) and in students (OR = 0.85; CI(95) = 0.75-0.97). Discussion: University staff and students reported high psychological distress, presenteeism and absenteeism. However, 33.8% of staff and 71.7% of the students were resilient. Amongst others, female gender, having children and having to self-isolate contributed to vulnerability. Exercise contributed to resilience. Conclusion: Resilience occurred much more often in students than in staff, although psychological distress was much higher in students. This suggests that predictors of resilience may differ from psychological distress per se. Hence, interventions to improve resilience should not only address psychological distress but may also address other factors.